The Contribution of Family Cohesion And Self-Efficacy on the Mental Health of Older Adults: A Survey Conducted in Aceh, Indonesia - Sufyan Anwar; Sukma Elida; Khairunnas (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Mental illness is recognized as a critical global issue and is a critical aspect of health problems, especially in older adults.Many studies analyze the correlation between self-efficacy and mental health. Still, studies that analyze the correlation between family cohesion and mental health among older adults in Aceh remainlimited.Methods: This study employeda survey method. The survey was carried out on older adults aged 60 years or more by applying a cross-sectional design with the number of samples was 483. At the same time, the data collection technique was done for four months in 2019. A logistic regression test was conducted for statistical analysis to answer the research hypothesis.Results: The finding of this study proved that family cohesion (OR> 3, p<0.001)and self-efficacy (OR > 2, p<0,001) were correlated with the mental health of older adults.Conclusions: The researchers conclude that families with good cohesion and older adults with high self-efficacy can support and improve the mental health of older adultsin Aceh.